Antioxidantal and histopathological effects of mirazid on gentamicin-induced renal damage in rats (Journal of Biochemistry, Microbiology and Biotechnology, 2015)
The present study evaluates the biochemical effect of mirazid(MZ) in rats of GMtamicin(GM)- induced renal damage. Albino male rats (Rattus norvegicus), weighing 40–50 g were divided into 6 groups; normal saline, orally trated mirazid 10 mg/kg, GM 100mg/kg, intraperitoneally (i.p) for 10 days, MZ at 2.5, 5, and 10 mg/kg, per oral for 10 days with the same concentration of GM, MZ administered concurrently with GM for 10 days. We investigated the effects of MZ on GM-induced nephrotoxicity. GM treatment caused nephrotoxicity as evidenced by marked elevation in serum Cr and blood urea (152.3 ± 8.6 mg/dL, 1.6 ± 0.12 mg/dL resp) when compared to the saline treated group. GM administration increased renal MDA and NO GMeration but decreased SOD and CAT activities, and GSPx (glutathione peroxidase) compared to normal control. MZ administration with GM injections caused significantly decreased MDA, NO GMeration and increased SOD, CAT activities and GSPx activity when compared with GM alone. Histopathological analysis revealed epithelial loss with intense+granular deGMeration in GM treated rats, whereas MZ decrease the severity of GM-induced renal damage. To conclude, our data suggest that MZ exhibits some antioxidantal effect against GM nephrotoxicity, as it has a potent scavenger of free radicals to prevent the toxic effects of GM at both the biochemical and histological level and further studies on its mechanism of action and side effects are wanted.